Euro area imbalances: How much could an expansion in the North help the South? - Oliver Picek; Enno Schröder (Institut für Makroökonomie und Konjunkturforschung (IMK), Hans-Böckler-Stiftung, 2017)
We run simulations of current account rebalancing scenarios in the Euro Area and the European Union based on a closed multi-country input-output model. The spillover effects of domestic demand booms in the Northern European surplus countries are non-negligible, but not large. While they cannot on their own create a meaningful upswing in the former Southern European deficit countries, they could be an important element thereof. In particular, a Northern expansion can create the necessary policy space for a domestic demand-driven expansion in the European South by relaxing the balance of payments constraint. Then, a coordinated asymmetric expansion in the Euro Area could alleviate the unemployment crisis in the European South. – – Auf Grundlage der Simulationen eines geschlossenen multi-regionalen Input-Output Modells berechnen wir die Effekte einer Rückkehr zu ausgeglichenen Leistungsbilanzen im Euroraum und der Europäische Union. Die "Spillover-Effekte" von Expansionen der Nachfrage in den nordeuropäischen Überschussländern sind quantitativ nicht vernachlässigbar, aber nicht herausragend. Obwohl sie für sich genommen nicht ausreichen, um in den südeuropäischen Ökonomien einen nachhaltigen Aufschwung anzustoßen, könnten sie ein wichtiger Bestandteil eines solchen sein. Insbesondere kann die Expansion im Norden den notwendigen Spielraum für eine eigene Nachfragesteigerung im europäischen Süden schaffen, indem sie die Zahlungsbilanzbeschränkungen der Südländer durch eine Verbesserung der Handelsbilanz abschwächen. Insgesamt könnte eine solche koordinierte, aber asymmetrische Expansion im Euro-Raum die Krise im europäischen Süden wesentlich lindern.
urn:nbn:de:101:1-201707123530
Keywords: F45; F32; F15; 330; Current Account Imbalances; Current Account Rebalancing; Euro Crisis; Euro Zone; Domestic Demand Expansion; European Union